ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI MELAKUKAN PEMERIKSAAN PAP SMEAR PADA WANITA USIA SUBUR - Sri Aminingsih; Tunjung Sri Yulianti (KOSALA : Jurnal Ilmu Kesehatan, 2020)
Background. One cause of death of women in Indonesia is cancer, one of which is cervical cancer. According to the 2013 Riskesdas data the incidence of cancer in Central Java was 2.1% with 1.2% being cervical cancer. Cervical cancer swallows many female victims in Indonesia, although it should be prevented by making efforts to prevent and detect early, one of them by carrying out a pap smear examination. The Aim of the Study. Knowing the factors that affecting motivation conducting pap smear examination in woman of childbearing age. Subject and Method. The research was analytic correlation design. The population in this study were women of childbearing age in the village of Wiragunan in September 2019 to March 2020 totaling 60 respondents. The sampling technique used is saturation sampling technique. The results of the study were analyzed using the Chi-Square Correlation Test. Result. Respondents with high knowledge were 44 (73.33%), who had low knowledge of 16 respondents (26.67%). High family support there are 43 respondents (71.67%), low family support 17 respondents (28.33%). While respondents with high motivation 42 (70%) and low motivation 18 (30%). The results of the Chi Square analysis of the level of knowledge (p = 0.001), family support (p = 0.001) on the motivation to do the pap smear. Conclusion. There is a relationship of knowledge about cervical cancer with the motivation to conduct pap smears in women of childbearing age. And there is a relationship of family support with the motivation to do a pap smear test on women of childbearing age. Keywords : cervical cancer, family support, knowledge, motivation, pap smear test Korespondensi: Sri Aminingsih. STIKES PANTI KOSALA SURAKARTA. Jalan Raya Solo - Baki Km. 4 Gedangan, Grogol, Sukoharjo, Jawa Tengah. Email: s.aminingsih@yahoo.co.id.